Escalating Risks: How North Korea’s Weapons Program Challenges Japan’s Security Framework - Amin, MD Ashraful; Fahim, Azizur Rahman; Hasan, Mehedi; Islam, Md. Masbahul; Jubair, Hassan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This paper explores the complex security challenges Japan faces in response to North Korea’s advancing weapons program and the implications for regional stability in East Asia. North Korea’s growing missile and nuclear capabilities pose significant threats, driving Japan to reconsider its security policies within the constraints of its pacifist constitution and longstanding U.S. alliance. This study analyzes Japan's adaptations to its Self-Defense Forces, increased defense spending, and enhanced missile defense systems as part of a strategic shift toward greater security autonomy. In a comparative analysis, Japan’s approach is evaluated alongside the security frameworks of South Korea and the United States, while considering the roles of China and Russia as influential regional actors. The study follows a qualitative framework based on secondary data. Policy recommendations emphasize the need for strategic flexibility, advancements in missile defense technology, and multilateral collaboration with allies. Long-term implications underscore how North Korea’s militarization could reshape the geopolitical landscape, necessitating a proactive, cooperative approach to maintain regional stability and deter potential conflict. This analysis offers insights into future directions for Japanese security policy and highlights areas for further research, including the impact of North Korea’s internal policies on regional security dynamics.